2015
DOI: 10.1139/cjpp-2014-0505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidative stress on Rho kinase II and smooth muscle contraction in rat stomach

Abstract: Recent studies have shown that both Rho kinase signaling and oxidative stress are involved in the pathogenesis of a number of human diseases, such as diabetes mellitus, hypertension, and atherosclerosis. However, very little is known about the effect of oxidative stress on the gastrointestinal (GI) smooth muscle Rho kinase pathway. The aim of the current study was to investigate the effect of oxidative stress on Rho kinase II and muscle contraction in rat stomach. The peroxynitrite donor 3-morpholinosydnonimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…In particular, the decrease of RhoA/ROCK expression, both at the transcriptional and translational levels, was reverted by the activity of SOD, thus demonstrating its link with oxidative stress [ 159 ]. However, these data disagree with a previous observation made on rat gastric muscle in which oxidative stress induced an activation of Rho kinase II with a consequent increase in Ach-induced contraction [ 160 ]. Nevertheless, in a later study, Singh and co-authors described a bimodal effect of oxidative stress in IAS basal tone.…”
Section: Role Of Oxidative Stress In Gastrointestinal Muscular Altcontrasting
confidence: 99%
“…In particular, the decrease of RhoA/ROCK expression, both at the transcriptional and translational levels, was reverted by the activity of SOD, thus demonstrating its link with oxidative stress [ 159 ]. However, these data disagree with a previous observation made on rat gastric muscle in which oxidative stress induced an activation of Rho kinase II with a consequent increase in Ach-induced contraction [ 160 ]. Nevertheless, in a later study, Singh and co-authors described a bimodal effect of oxidative stress in IAS basal tone.…”
Section: Role Of Oxidative Stress In Gastrointestinal Muscular Altcontrasting
confidence: 99%
“…Measurement of contraction in dispersed GSMCs. Contraction of isolated muscle cells was measured by scanning micrometry as described previously (23,24). In brief, aliquots of cell suspension from 10 of the rats each containing ~10 4 cells/ml were added to HEPES medium and randomly distributed into either control or progesterone-treated groups.…”
Section: Isolation Of Gsmcsmentioning
confidence: 99%
“…The cells were viewed using a x10 or x20 objective of an inverted Nikon TMS-f microscope (Nikon Corporation, Tokyo, Japan), and cell images were acquired using a Canon digital camera (Canon Inc., Tokyo, Japan) and ImageJ acquisition software (version 1.45s; National Institutes of Health, Bethesda, MA, USA). The length of 50 muscle cells treated with the contractile agent (ACh) was measured at random by scanning micrometry (23,24). This was then compared with the length of untreated cells.…”
Section: Isolation Of Gsmcsmentioning
confidence: 99%
“…In addition, ROCK inhibitor Y-27632 significantly inhibited the H 2 O 2 -elicited increase of basal tension, suggesting that H 2 O 2 may increase Ca 2+ sensitivity by regulation of the ROCK pathway. Multiple studies have demonstrated that H 2 O 2 can enhance the activation of ROCK and mediate vascular contraction [ 54 , 55 ]. In spontaneously hypertensive rats, increased ROCK activation was involved in the H 2 O 2 -induced contraction of mesenteric resistance arteries [ 55 ].…”
Section: Discussionmentioning
confidence: 99%